Guidance for the Interpretation of Continual Cuffless Blood Pressure Data for the Diagnosis and Management of Hypertension - Sola, Josep; Cortes, Meritxell; Perruchoud, David; De Marco, Bastien; Lobo, Melvin D.; Pellaton, Cyril; Wuerzner, Gregoire; Fisher, Naomi D. L.; Shah, Jay (Frontiers in Medical Technology, 2022)
Hypertension remains the leading risk factor for death worldwide. Despite its prevalence, success of blood pressure (BP) management efforts remains elusive, and part of the difficulty lies in the tool still used to diagnose, measure, and treat hypertension: the sphygmomanometer introduced by Samuel Siegfried Karl von Basch in 1867. In recent years, there has been an explosion of devices attempting to provide estimates of BP without a cuff, overcoming many limitations of cuff-based BP monitors. Unfortunately, the differences in underlying technologies between traditional BP cuffs and newer cuffless devices, as well as hesitancy of changing a well-implemented standard, still generate understandable skepticism about and reluctance to adopt cuffless BP monitors in clinical practice. This guidance document aims to navigate the scientific and medical communities through the types of cuffless devices and present examples of robust BP data collection which are better representations of a person's true BP. It highlights the differences between data collected by cuffless and traditional cuff-based devices and provides an initial framework of interpretation of the new cuffless datasets using, as an example, a CE-marked continual cuffless BP device (Aktiia BP Monitor, Aktiia, Switzerland). Demonstration of novel BP metrics, which have the potential to change the paradigm of hypertension diagnosis and treatment, are now possible for the first time with cuffless BP monitors that provide continual readings over long periods. Widespread adoption of continual cuffless BP monitors in healthcare will require a collaborative and thoughtful process, acknowledging that the transition from a legacy to a novel medical technology will be slow. Finally, this guidance concludes with a call to action to international scientific and expert associations to include cuffless BP monitors in original scientific research and in future versions of guidelines and standards.